Music in Dongting Hu Area in China - Mengwan , Tu; Sondhiratna, Thanyawat (Journal of Roi Kaensarn Academi, 2024)
Dongting Hu is one of the five major lakes in China which was called “Eight hundred miles of Dongting”. Its main lake is located in Hunan, including East Dongting Hu which is located in Yueyang City, South Dongting Hu which is located in Yiyang City, and West Dongting Hu which is located in Changde City. As one of the important birthplaces of Chu culture, the music in Dongting Hu region is rich and lively. The area around Dongting Hu has a long history of fishing and farming culture, and local residents mainly focus on fishing and farming. Therefore, the fisherman culture and farming culture have a significant influence on music. Labors will compose various kinds of music such as fishing songs, folk songs, fishing drums, and labor songs in their daily life, which are often themed with the life experience, work scenes and emotions of local residents that full of love for labor and perception of life.